Accounting Systems and Human Resources: Enhancing Financial Timeliness and BOS Disbursements: Sistem Akuntansi dan Sumber Daya Manusia: Meningkatkan Ketepatan Waktu Laporan Keuangan dan Pencairan Dana BOS - Perdana Juliartha Gunansya; Fityan Izza Noor Abidin (Universitas Muhammadiyah Sidoarjo, 2022)
This study discusses the application of accounting information systems and the quality of human resources in realizing the timeliness of financial reporting and disbursement of BOS funds 2020. The purpose of this study is to find out how the implementation of accounting information systems and the quality of human resources in realizing the timeliness of financial reporting and disbursement BOS Fund. This study uses a qualitative research method with a phenomenological approach where data collection is obtained from interviews and observations. The data analysis technique used in this research is data reduction, data reduction is done by collecting important information and then the data is grouped according to topic so that it can provide a clearer picture and make it easier to collect data. The results showed that the research subjects had implemented the system determined by the government and improved the quality of human resources in order to have the confidence, skills and experience in order to realize the proper reporting of BOS funds so that the disbursement of BOS funds could also be carried out properly. Keywords - Accounting Information Systems, Human Resources, Timeliness of Reporting, Disbursement of BOS Funds. Highlights: The study focuses on the implementation of accounting information systems and the quality of human resources in achieving timely financial reporting and disbursement of BOS funds. The qualitative research method with a phenomenological approach is used, involving interviews and observations for data collection. Data analysis technique includes data reduction, which involves collecting important information and grouping it by topic for a clearer understanding and easier data collection. Keywords: Accounting Information Systems, Human Resources, Timeliness of Reporting, Disbursement of BOS Funds, Qualitative Research Method